The effects of holding time and the sweeping nitrogen gas flowrates on the pyrolysis of EFB using a fixed–bed reactor - Alina Rahayu, Mohamed (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.